Do non-mammary conditions influence patients’ cosmetic perception after breast conserving surgery? - de Oliveira-Junior, Idam; da Silva, Fabíola Cristina Brandini; Sarri, Almir José; Vieira, René Aloísio da Costa (Frontiers in Oncology, 2025)
IntroductionCompared to mastectomy, breast-conserving surgery (BCS) guarantees equivalent local control and survival, with lower morbidity and better quality of life (QOL), even in the long term. However, some BCS patients consider the cosmetic result to be unsatisfactory, which may affect QOL.Material and methodsThis prospective, cross-sectional study included patients who underwent BCS. The patients answered the European Organization for Research and Treatment of Cancer Quality of Life questionnaire (EORTC QLQ) - C30, EORTC QLQ-BR23 and Breast Cancer Treatment Outcome Scale (BCTOS) questionnaires, underwent cosmetic breast self-assessment and had their breasts photographed. The photographs were analyzed using Breast Cancer Conservative Treatment. Cosmetic results (BCCT.core). For the categorical variables, the frequencies were calculated; for the numerical variables, the mean and standard deviation. The BCCT.core results were compared with the cosmetic results of the patients, which yielded four possible results: concordant satisfaction, discordant satisfaction, concordant dissatisfaction and discordant dissatisfaction (satisfactory BCCT.core evaluation but patient dissatisfaction). The kappa test was used for agreement between categorical variables. Student’s t test and Mann-Whitney were used to assess the relationship between QOL and cosmetic results. The ANOVA were performed with the adjusted Bonferroni correction to compare the four groups.ResultsA total of 300 patients were evaluated, 298 underwent self-assessment of the breasts (76.8% satisfactory results and 23.2% unsatisfactory) and 297 underwent BCCT.core evaluation (29.9% satisfactory results and 79.1% unsatisfactory), which had a kappa of 0.095 (p = 0.01). In the self-assessment, patients with unsatisfactory cosmetic results had worse overall health, physical, functional, emotional, cognitive, and social capacity, fatigue, pain, dyspnea, financial difficulties, body image; future prospects, side effects, breast symptoms, functional aspects, cosmetics and edema. When we used software evaluation, these relationships did not have the same proportions. In patients with “discordant dissatisfaction”, higher pain scores and worse functionality on the treated side were found.ConclusionAn unsatisfactory cosmetic result was associated with worse QOL, which may be associated with other factors, such as breast pain and functionality.